The Effect of Digital Financial Literacy, Digital Lifestyle, and Perceived Ease of Use on the Financial Management of E-Wallet Users among Students in Pontianak - Nia Aprianti; Dedi Hariyanto; Heni Safitri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to identify the effect of digital financial literacy, digital lifestyle, and perceived ease of use on the financial management of student e-wallet users in Pontianak City. This study uses an associative method. The population in this study consists of all active students domiciled in Pontianak City, with a sample of 150 respondents determined using purposive sampling techniques. Instrument testing techniques in this study include validity and reliability tests. Furthermore, the classical assumption tests used consist of normality, linearity, and multicollinearity tests. Hypothesis testing was carried out using multiple linear regression analysis, correlation coefficient, coefficient of determination, simultaneous test (F test), and partial test (t test). Based on the simultaneous test results, the calculated F value is 47.857 > the F table value of 2.67 with a significance level of 0.000 < 0.05, which means that digital financial literacy, digital lifestyle, and perceived ease of use simultaneously have a positive and significant effect on the financial management of student e-wallet users in Pontianak City. The partial test results show that digital financial literacy, digital lifestyle, and perceived ease of use individually have a positive and significant effect on financial management.